Preiskava tankih večplastnih kovinskih struktur v področju ohmskega kontakta tranzistorja z metodo AES - Praček, Borut (Kovine zlitine tehnologije, 1999)
Transistor ohmic contact is an electrical contact between a thin metal layer and semiconductor. It is characterized with a very small resistance, non-aimable feature and linear current-voltage characteristic. The paper describes the AES characterization of defective ohmic contact by means of depth profile analysis of AuSnNiTi thin metallic structures. Auger electron spectroscopy is used for depth profiling in elemental concentration in combination with ionic sputtering of the samples. The influence of contaminants to thin metallic layer adhesion is also considered. Test results show specific technological inconsistencies in thin film fabrication process.
Keywords: kovine; električni kontakti; večplastne strukture; nečistoče; površine